Tracing the Correlation Between Islamic Law and Economics in Indonesia: Theoretical and Practical Perspectives - N Nuha; Noornajihan Jaafar; M Muthoifin; Jihan Husna Srifyan; Wildan Mahir Muttaqin (Walidem Institute and Publishing, 2024)
This study aims to explore and analyze the correlation between Islamic law (fiqh) and Sharia economics in Indonesia, both from a theoretical and practical perspective. The research methods used are literature study and descriptive analysis. Data was collected through a literature review from various relevant sources, including academic literature, official documents, and case studies related to the implementation of Islamic law in the economic context in Indonesia. The results showed that the correlation between Islamic law and Sharia economics in Indonesia is very significant. Fiqh, as the foundation of Islamic law, has a major impact on the development and implementation of Islamic economic principles in Indonesia. Various aspects of Islamic law such as muamalah (economic transactions), zakat, waqf, and others, provide a strong theoretical foundation for the practice of Islamic economics in Indonesia. However, there are challenges in integrating fiqh with Islamic economic practices in Indonesia, including in terms of harmonization between the principles of Islamic law and existing government regulations. In addition, public awareness and understanding of Islamic law and sharia economics also play an important role in the successful implementation and development of the sharia economy in Indonesia.